Trigonometric widths of classes of periodic functions of many variables - Derev’yanko, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain exact-order estimates for the trigonometric widths of the classes $B^{Ω}_{pθ}$ of periodic functions of many variables in the space $L_q$ for some relations between the parameters $p$ and $q$.